An approach to e-workflow systems with the use of patterns - Ndeta, John; Katriou, Stamatia-Ann; Siakas, Kerstin (International Journal of Entrepreneurial Knowledge, 2015)
In today’s highly competitive and rapidly changing environment, e-businesses constantly have to modify their business processes, i.e. the flow of documents and tasks in a business also known as workflow. More flexible Workflow Management Systems are required to support these constantly changing processes. In this research a platform independent architecture for the design of e-workflow systems is illustrated. The architecture includes an information pool, namely a Workflow Pattern Repository, which contains patterns, which are repeatable solutions to reoccurring problems, in order to make the system more apt to change and assist the workflow designer/user in defining workflows faster and more accurately. The patterns in the repository are in the form of UML activity diagram templates. A straightforward input format for storing patterns in the repository is provided along with an example of its practical application. <a title="Jaroslav Belás, Lenka Gabčová Reasons for satisfaction and dissatisfaction of bank customers. Study from Slovakia and the Czech republic." href="https://ijek.org/files/IJEK_1-2015v3/ijek_1-2015,v.3_ndeta,j.katriou,s.siakas,k..pdf">